Towards an understanding of consumers' FinTech adoption: the case of Open Banking. Issue 4 (5th April 2022) - Chan, Rebecca; Troshani, Indrit; Rao Hill, Sally; Hoffmann, Arvid
Abstract : Purpose: This study aims to identify key factors driving consumers' adoption of Open Banking. It extends the Unified Theory of Acceptance and Use of Technology (UTAUT) by integrating perceived risk, initial trust and financial literacy into an overarching conceptual model. Design/methodology/approach: Measurement items of the theoretical constructs included in the conceptual model were adapted from related literature and a set of hypotheses was developed. The hypotheses of the conceptual model were subsequently assessed with partial least squares structural equation modeling using a dataset of 456 Australian survey respondents. Findings: The model has strong explanatory power with an R 2 of 69.5%. Performance expectancy, effort expectancy, social influence and perceived risk are direct antecedents of consumers' usage intention of Open Banking. Social influence has a strong mediating effect on usage intention through performance expectancy. The effect of perceived risk is alleviated by effort expectancy and initial trust, while initial trust positively affects the effects of performance expectancy and effort expectancy on consumers' usage intention of Open Banking. Finally, financial literacy lowers initial trust towards Open Banking, possibly inducing consumer skepticism. Practical implications: The results suggest that practitioners should focus on performance expectancy as a primary driver of Open Banking adoption, while understanding the role of other drivers, such as social influence and perceived risk in developing marketing strategies. Policy makers are recommended to adopt a governance approach to build initial trust amongst consumers. Originality/value: This research contributes by providing an integrated and comprehensive model for explaining consumers' FinTech adoptions by extending the existing technology adoption model UTAUT to the Open Banking domain and integrating perceived risk, initial trust and financial literacy, thereby advancing and enriching the conceptual horizon of the extant literature.